Implementation of Religious Moderation in Building Social Harmony in Educational Environments - Binta Sajida; Asep Ediana Latip; Fatimah Azzahra (UIN Mataram, 2026)
Religious moderation plays an essential role in fostering tolerance and social harmony within pluralistic higher education environments. However, students’ understanding of religious moderation often remains conceptual and is not fully reflected in daily social practices. This study aims to describe the level of religious moderation implementation, analyze students’ social harmony, and examine the relationship between the two variables in higher education. A quantitative approach with a survey method was employed. Data were collected through an online questionnaire distributed via Google Forms to 32 students and analyzed using descriptive percentage analysis. The findings indicate that the implementation of religious moderation is categorized as good, as shown by high levels of agreement on indicators of understanding and institutional support. Students’ social harmony is also relatively high, reflected in mutual respect for religious differences and comfort in interfaith interactions. The results further reveal a positive relationship between religious moderation and social harmony. This study highlights the importance of strengthening religious moderation to promote a tolerant, inclusive, and harmonious campus environment.